How Deep Was the Impact of the Economic Crisis in Vietnam? : A Focus on the Informal Sector in Hanoi and Ho Chi Minh City - Cling, Jean-Pierre; Chi, Nguyen Huu; Razafindrakoto, Mireille; Roubaud, Francois (World Bank, Washington, DC, 2017)
Vietnam is one of the only South East Asian emerging economies not to have gone into recession in 2009 in the wake of the world crisis. Nonetheless, it has been affected deeply by the crisis, as shown by all macro-economic indicators. The yearly growth rate of Gross Domestic Product (GDP) has been slowing down from 8.5 percent in 2007 to 6.3 percent in 2008 then 5.3 percent in 2009, before recovering to 6.5 percent in 2010. Overall, because of productivity gains and rapid growth of the labour force due to the 'demographic dividend' which is currently peaking, an average economic growth of 7.5 percent such as attained during 2000-2008 is hardly sufficient to absorb new entrants on the labour market. Even with such a high growth rate, around one fourth of new entrants end up in the informal sector. The latter thus absorbs the labour surplus which agriculture and the formal sector are unable to employ. Several quick qualitative assessments of the impact of the crisis have been conducted in Asia and especially in Vietnam, based on a small number of interviews in some selected industries. They indeed put in evidence the impact of the crisis on the informal sector in terms of employment, number of hours worked and wages. But, due to the lack of data, no quantitative study of the impact of the crisis on the informal sector had been conducted until now. This is precisely the objective of this policy brief, based on the results of two rounds of Household Business & Informal Sector (HB&IS) surveys conducted on a statistically representative sample in Hanoi and HCMC in 2007 and 2009 within an international research project between Vietnam's General Statistics Office (GSO) and the French Institute. This brief can be usefully complemented by two companion papers: the first one presents the adjustment of the labour market and the informal economy nationwide the second one provides detailed results on the dynamics of the informal sector in the two main cities between 2007 and 2009.